The strange case of the flying spiders. (1st August 2022) - Allen, Michael
Abstract : Researchers in Lebanon and the US have modelled the interactions between spider silk threads and the atmosphere to explain how spiders can exploit the positive electric potential of Earth's atmosphere to fly and disperse.